Old and Young in Thucydides: Experience, Learning, and Themistocles - Tsakmakis, Antonis (Araucaria, 2017)
Although Thucydides does not shed light on the reasons and the historical facts relating to his departure from Athens, he is certainly far clearer on the effects that this event had on his work. He explicitly recognizes that the condition of exile offered him the rather unique possibility to observe the conflict from the Peloponnesian side as well and to follow the course of events without being distracted by troubles or other activities (καθ’ ἡσυχίαν). In this study I emit the hypothesis that in 5.26 Thucydides makes an indirect allusion to the fact that a life of quietude, which liberates the eminent thinker from engagement in political life, is the path leading to intellectual production. This reading can help us recognize the intellectual affinities between Thucydides and the Athenian thinkers of the end of the fifth century BC and more particularly with Socrates’s circle.